Badanie Wpływu Współczynnika Przenikania Ciepła na Końcowy Stan Naprężenia w Sprężysto-Plastycznej Kuli Poddanej Procesowi Chłodzenia - Raniecki, B. (Engineering Transactions, 1967)
The subject of the present paper is study of the stress that appear in an elastic-plastic spherical body cooled (by immersing in a cold liquid) from a uniform initial temperature T0 to 0°C. The considerations are based on the results of [2] assuming a compressible material, linear strain-hardening and rejecting the influence of the temperature on the physical properties of the material. The paper contains also a discussion of the influence on the final state of stress, of the Biot number and the degree of strain-hardening. It is shown that the idealization consisting in the assumption of a temperature jump at the moment t = 0 in the boundary condition for the heat equation leads, for Biot numbers below 100, to an erroneous appraisal of the final value of the stress.